Notions about the Family and Ecuadorian Good Living - Calle García , Jorge Isaac; Calle Antón , Jorge Isaac (Journal of the University of Zulia, 2021)
The research aims to establish some notions about the Family and The Ecuadorian Good Living, it is addressed with the descriptive-documentary research strategy, with a focus on the analytical method. The importance lies in the link between both institutions, since by assuming Good Living as a set of rights to be satisfied respecting nature, the Family represents the first structure of responsibilities and rights of people and, in complying with them, it is also done from the consideration of the natural environment. In addition, Good Living implies placing equality as the central axis, as is the case with the Family. In the most relevant conclusion, it is maintained that the Republic of Ecuador grants constitutional supremacy to the Family and Good Living because, together, they incorporate ancestral rights, perspectives and conceptions adapted to the present, with schemes and contents that allow development.